Syria and Chile, recreation and memory in “Nahima: The long story of my mother” by Edith Chahín Curí - Yahla, Houda (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
Historical novel is the best way to recover ancestral customs and this play, “Nahima: A long story about my mother” (2013), written by Edith Chahín, a Chilean of Syrian origin woman, offers that. This fictional play revives the life lessons that recall the travel of a generation of Syrian immigrants to Latin America, between 19th and 20th centuries. Important to say is that the novel catches the reader´s attention because of its realism and all the detailed descriptions and the traditions of the dream home country. All these, make the book be a compilation of uses and customs that will remain thanks to writing. Taking side for uprooted families, the author leaps to criticize the politics of the Ottoman oppressor, due to the wars and problems that caused to Syria, provoking the exile of entire generations, included her parents´ one.